2014
DOI: 10.1093/brain/awu354
|View full text |Cite
|
Sign up to set email alerts
|

Genetic manipulation of adult-born hippocampal neurons rescues memory in a mouse model of Alzheimer’s disease

Abstract: In adult mammals, neural progenitors located in the dentate gyrus retain their ability to generate neurons and glia throughout lifetime. In rodents, increased production of new granule neurons is associated with improved memory capacities, while decreased hippocampal neurogenesis results in impaired memory performance in several memory tasks. In mouse models of Alzheimer's disease, neurogenesis is impaired and the granule neurons that are generated fail to integrate existing networks. Thus, enhancing neurogene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
82
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(89 citation statements)
references
References 77 publications
4
82
1
1
Order By: Relevance
“…Alternatively, the FMD may increase survival of newly-differentiated neurons, as observed in the dentate gyrus of alternate day-fed rodents (Lee et al, 2002; Mattson et al, 2001). The observed improvements in cognitive performance in the FMD cohort might be affected by an the increase in neurogenesis mediated by PKA/CREB-dependent regulation of NeuroD1 (Cho et al, 2012; Sharma et al, 1999), which is known to increase neuronal survival and differentiation of hippocampal progenitors (Roybon et al, 2009), enhance functional integration of new neurons, and alleviate memory deficits in a mouse model of Alzheimer’s disease (Richetin et al, 2015). …”
Section: Resultsmentioning
confidence: 99%
“…Alternatively, the FMD may increase survival of newly-differentiated neurons, as observed in the dentate gyrus of alternate day-fed rodents (Lee et al, 2002; Mattson et al, 2001). The observed improvements in cognitive performance in the FMD cohort might be affected by an the increase in neurogenesis mediated by PKA/CREB-dependent regulation of NeuroD1 (Cho et al, 2012; Sharma et al, 1999), which is known to increase neuronal survival and differentiation of hippocampal progenitors (Roybon et al, 2009), enhance functional integration of new neurons, and alleviate memory deficits in a mouse model of Alzheimer’s disease (Richetin et al, 2015). …”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, Demars et al [91] have reported that APPswe/PS1ΔE9 mice exhibit severe impairments in hippocampal neurogenesis at as early as two months of age. These decreases in neurogenesis within the DG have been associated with cognitive impairments linked with AD [9295]. In addition, Boekhoorn et al [96] have reported that proliferation does occur in presenile Alzheimer hippocampus (patients ranging from 63 to 70 years of age), and this proliferation reflects glial and vascular-associated changes in the CA1-3 areas but not neurogenesis in the DG.…”
Section: Discussionmentioning
confidence: 99%
“…In APPxPS1 mouse AD models, there are only limited numbers of new neurons generated and the capacity of the new granule cells is reduced in a sex‐unbalanced manner (Richetin, Petsophonsakul, Roybon, Guiard, & Rampon, 2017). NSC transplantation slowed the disease progression in an AD mouse model (Blurton‐Jones et al, 2009), while directed expression of a transcription factor, Neurod1, in cycling hippocampal progenitors could produce population of highly connected new neurons and restore spatial memory in AD mouse model (Richetin et al, 2015). …”
Section: Cellular Changes In Aging and Admentioning
confidence: 99%